2017
DOI: 10.1108/imds-04-2016-0139
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain contracting coordination for fresh products with fresh-keeping effort

Abstract: Purpose-Fresh product loss rates in supply chain operations are particularly high due to the nature of perishable products. This paper aims to maximize profit through the contract between retailer and supplier. The optimized prices for the retailer and the supplier, taking the fresh-keeping effort into consideration, are derived. Design/methodology/approach-To address this issue, we consider a two-echelon supply chain consisting of a retailer and a supplier (i.e., wholesaler) for two scenarios: centralized and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 49 publications
1
33
0
Order By: Relevance
“…First, we solve the profit function for the retailer where the retailer's sales margin is m � p − w; using the inverse induction method, we obtain first and second derivatives from equation (19) and set the first derivatives equal to zero:…”
Section: Case 4: Retailer's Bs Investment Under the Revenue-mentioning
confidence: 99%
“…First, we solve the profit function for the retailer where the retailer's sales margin is m � p − w; using the inverse induction method, we obtain first and second derivatives from equation (19) and set the first derivatives equal to zero:…”
Section: Case 4: Retailer's Bs Investment Under the Revenue-mentioning
confidence: 99%
“…According to Qian et al [45], a case study of Hohhot found that the setting of revenue-sharing contracts has increased the total profit of the dairy industry by 12.49%, and a win-win situation could be achieved under certain circumstances. On the basis of the characteristics of perishable foods, Zheng et al [46] designed a fresh food supply chain (FPSC), taking the cost of freshness preservation into account, and the results showed that fresh-keeping cost-sharing and the revenue-sharing contract has the best coordination effect on FPSC. Taking the field of Internet of Things as a research object, Yan et al [47] improved the revenue-sharing contract for the fresh agriculture supply chain to discuss the impact of fresh agricultural products on costs of controlling freshness and market demand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a two-echelon decision-making model consisting of a loss-averse farmer and a loss-neutral company, Fu et al [32] found that a high guaranteed price decided by the company can reduce the losses of farmers caused by price uncertainty; however, such pricing may breed laziness among the farmers in sustainable agricultural practice and reduce their activeness in supplying agri-foods. As an important indicator of the quality of fresh produce, freshness preservation also influences the quality of agri-foods and revenue of participants [33]. When consumers have increased sensitivity in high-level green agri-foods, members of the supply chain are willing to participate in coordination [34].…”
Section: Relevant Literature Reviewmentioning
confidence: 99%